Nifedipine-Induced Changes in the Electrohysterogram of Preterm Contractions: Feasibility in Clinical Practice. (16th June 2010) - Vinken, Maartje P. G. C.; Rabotti, C.; Mischi, M.; van Laar, J. O. E. H.; Oei, S. G.
Abstract : Objective . Evaluating changes in the power spectral density (PSD) peak frequency of the electrohysterogram (EHG) caused by nifedipine in women with preterm contractions. Methods . Calculation of the PSD peak frequency in EHG contraction bursts at different times of nifedipine treatment in women in gestational age 24 to 32 weeks with contractions. Results . A significant (P < .05 ) decrease of PSD peak frequency between EHG signals measured before and 15 minutes after administration of nifedipine. A significant (P < .05 ) decrease in PSD peak frequency comparing signals recorded within 24 hours after administration of nifedipine to signals 1 day after tocolytic treatment. A higher average PSD peak frequency for patients delivering within 1 week than that for patients delivering after 1 week from nifedipine treatment (P > .05 ). Conclusions . EHG signal analysis has great potential for quantitative monitoring of uterine contractions. Treatment with nifedipine leads to a shift to lower PSD peak frequency in the EHG signal.